2020
DOI: 10.1121/10.0002275
|View full text |Cite
|
Sign up to set email alerts
|

Brightness perception for musical instrument sounds: Relation to timbre dissimilarity and source-cause categories

Abstract: Timbre dissimilarity of orchestral sounds is well-known to be multidimensional, with attack time and spectral centroid representing its two most robust acoustical correlates. The centroid dimension is traditionally considered as reflecting timbral brightness. However, the question of whether multiple continuous acoustical and/or categorical cues influence brightness perception has not been addressed comprehensively. A triangulation approach was used to examine the dimensionality of timbral brightness, its robu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…In order to further explicate the observed effects, we constructed simple models of task performance. We followed the literature that has used the spectral centroid (SC; center of gravity of the spectral energy distribution of the sound signal) as a feature for quantifying auditory brightness perception 3 , 26 , 27 , 36 . We focus on modelling an adaptive response criterion, which bears similarity to previous work on pitch content effects 19 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further explicate the observed effects, we constructed simple models of task performance. We followed the literature that has used the spectral centroid (SC; center of gravity of the spectral energy distribution of the sound signal) as a feature for quantifying auditory brightness perception 3 , 26 , 27 , 36 . We focus on modelling an adaptive response criterion, which bears similarity to previous work on pitch content effects 19 .…”
Section: Resultsmentioning
confidence: 99%
“…The attribute of auditory brightness has commonly been considered as a critical contributor to timbre perception and has been considered as being determined by the instantaneous spectrum 3 , 35 , 36 processed in auditory cortex 37 , 38 . Yet, relatively little is known about neural underpinnings of spectral adaptation effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such use will be restricted to western instruments as the model relies on human identification of descriptors that was limited to western musical instruments. A recent study suggested that timbre brightness perception is primarily perceived by acoustical cues (Saitis & Siedenburg, 2020). Prompting us to observe the potential of using semantic descriptors for identification of timbral qualities commonly used in music production.…”
Section: Introductionmentioning
confidence: 99%
“…Traversing spectrum values largely follows a transition from a sine wave to a square wave to a sawtooth; starting with the fundamental frequency, gradually adding oddharmonics, and then adding even ones. Brightness, experimentally correlated to spectral centroid [7], is recreated as a frequency filter. The filter is either low-pass or high-pass, depending on whether the parameter is low or high respectively.…”
Section: Synthesis Modelmentioning
confidence: 99%